Driving Forces Behind Adopting English Medium Instruction in Nepalese Community Schools - Karki, Tek Mani (Studies in ELT and Applied Linguistics, 2025)
Community schools in Nepal seem to have shifted the existing medium of instruction (MOI) to English nowadays. In this context, the implementation of the English-as-a-medium-instruction (EMI) policy has become a contemporary issue for researchers to study. This paper explored the driving forces behind the enactment of the EMI policy at community school in Nepal. This study has used the blended qualitative approaches of ethnography and case study—mini-ethnographic case study (MECS). Selecting an EMI adopted community school as a case and EMI as a phenomenon, I interviewed and informally interacted with purposively selected participants—the head teacher, three teachers, a School Management Committee (SMC) representative, a Parent-Teacher Association representative, and three parents—to collect the qualitative information. I analyzed and interpreted the data categorizing them into themes using the ATLAS.ti software. They implemented the EMI policy thinking that it would facilitate them for ‘bikau’ of the students in the market (salability of production in the market), ‘tikau’ of the institution (maintainability of the school), and with the supposition that it would be a hallmark of social supremacy. The stakeholders seem to have been influenced by the neoliberal perspective while adopting and continuing the EMI policy in their school.